Climate change and its implications : which way now? (Commonwealth Foundation LondonGB, 2007)
Highlights key issues of relevance to the theme of the 2007 Commonwealth Finance Ministers Meeting viz, to idenfity strategies for ministers and CSOs to address poverty reduction issues in the context of the climate change debate and work towards a consensus on measures needed to mitigate climate change for the benefit of all Commonwelath member countries.
Keywords: CLIMATE CHANGE